Morphological and genetic variation in populations of Sitana marudhamneydhal and the validity of Sitana attenboroughii - Balan, A.; Jude, D.; Narayanan, Surya; Varma, Sandeep; Deepak, V. (Zootaxa, 2021)
Dewlap morphology and body ratios are two of the main morphological characters used in delimiting Sitana spp. It becomes a statistical limitation when small samples are used in species descriptions, as outliers can be picked to be described as a distinct species. Genetic data has been used to support the distinctness of a species in Sitana. However, species with shallow genetic divergence becomes a problem if not thoroughly examined. We examine and report our findings on morphological and genetic differences in two populations of Sitana marudhamneydhal and one population of S. attenboroughii. The shallow genetic divergence and overlapping morphology shows that Sitana attenboroughii is a junior synonym of Sitana marudhamneydhal